Analisis subsidi perikanan non BBM di Kabupaten Aceh Besar, Provinsi Aceh - Zainal A. Muchlisin; Nur Fadli; Arifsyah M. Nasution; Rika Astuti; Marzuki Marzuki; Darmawi Musni (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The objective of the present study was to analyze the budgetary trends and the effectiveness of fisheries subsidies in Aceh Besar district. The literature and survey methods were utilized in this study. The secondary data of Aceh Besars budget documents in the period of 2010-2012 and key person interviews with fishermen leaders were conducted to analysis the subsidy trend and fishermen perception. The data was collected in May through July 2012. The results showed the budget allocation to the fisheries sector were increased from year to year, in 2010 the total budget for the fisheries sector was Rp1, 9 billions (equivalent to 0.34% of total buget or 1.40% of the development budget allocation/indirect consumption), in it was increased to Rp2, 9 billion in 2011 (or 0.42% of total budget or 1.47% of the development budget allocation), then increased sharply in 2012 to Rp9, 2 billion (an increase of over 630%) from the previous year, equivalent to 1.11% of the total budget. In 2010, the proportion of subsidies were given mostly for aquaculture sub-sector, which reached 84% of the total budget that was managed by the Department of Marine and Fisheries of Aceh Besar, whereas in 2011 the proportion of subsidies occurred balance between aquaculture and capture fishery sub sectors. However, in 2012 most of the budget DKP Aceh Besar (63%) was allocated to the capture fishery sub-sector. The results of the study showed that fisheries subsidies by the Government of Aceh Besar district especially in the last two years have not yet met the criteria of sustainable fisheries subsidies. Keywords: fisheries subsidies, budget allocation, and Aceh Besar